2021
DOI: 10.3390/app11093820
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of an Innovative Hybrid Energy Storage System for Residential Buildings in Continental Climates

Abstract: With the aim of contributing to achieving the decarbonization of the energy sector, the environmental impact of an innovative system to produce heating and domestic hot water for heating demand-dominated climates is assessed is evaluated. The evaluation is conducted using the life cycle assessment (LCA) methodology and the ReCiPe and IPCC GWP indicators for the manufacturing and operation stages, and comparing the system to a reference one. Results show that the innovative system has a lower overall impact tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The results showed that the total impact of heat pumps could decrease as the percentage of renewable energy sources in the UK electricity mix increases, while still exceeding the impact of the gas boiler. Llantoy et al [18] performed an LCA for a lifespan of 30 years to compare the environmental impact of an innovative hybrid energy storage system for heating and domestic hot water production in continental climates with the environmental impact of a traditional system. The results of the analysis, performed through the ReCiPe and the IPCC global warming potential GWP indicators, showed that the total impact of the innovative hybrid energy storage system was lower than the reference one.…”
Section: Life Cycle Assessment Applied To Buildingsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that the total impact of heat pumps could decrease as the percentage of renewable energy sources in the UK electricity mix increases, while still exceeding the impact of the gas boiler. Llantoy et al [18] performed an LCA for a lifespan of 30 years to compare the environmental impact of an innovative hybrid energy storage system for heating and domestic hot water production in continental climates with the environmental impact of a traditional system. The results of the analysis, performed through the ReCiPe and the IPCC global warming potential GWP indicators, showed that the total impact of the innovative hybrid energy storage system was lower than the reference one.…”
Section: Life Cycle Assessment Applied To Buildingsmentioning
confidence: 99%
“…The lifetime of the entire analysis was assumed to be 90 years, while the lifespan and the number of replacements of each system during the 90 years were calculated according to the lifetime of the various systems. Conventionally, the LCAs of products or buildings are performed with a lifetime ranging from 30 to 50 years [12,18,19,53,54], without considering any external variations (e.g., climate change) to the system boundary that could alter the environmental impact of the systems or the buildings. Following the conventional methodology, the LCA for 90 years (hereinafter referred to as LCA b ) was assessed by considering the same weather data for the entire period, as shown in Figure 2a.…”
Section: Goal and Scope Definitionmentioning
confidence: 99%
See 3 more Smart Citations